Optimasi Informasi Diagnostik Citra Axial MRI Brain antara Sekuen SWI dan T2 FLASH 2D pada Kasus Tumor Otak - Farida, Siti Nur; Sulaksono, Nanang; Kurniawati, Ary (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: Pulse gradient echo sequences use varying RF excitation pulses and with NMV flips through various angles (not just 90Â°). Gradient echo has a sensitive susceptibility effect in detecting the presence of blood products (hemorrhage) and calcifications in brain tumors. The SWI and T2 FLASH 2D sequences are part of the pulse sequence gradient echo, where the SWI sequence is a 3D velocity compensated gradient echo and the T2 FLASH 2D sequence is a 2D multi-slice gradient echo. This study aims to determine the differences in axial image diagnostic information and determine the most optimal axial image diagnostic information in MRI brain examinations between SWI and T2 FLASH 2D sequences in brain tumor cases.Methods: This type of research is quantitative with an experimental approach. Data was taken in March 2024 at the Radiology Installation of RSUP Dr. Sardjito Yogyakarta. The sample in this study was 10 patients with brain tumor cases. An assessment was carried out by 2 respondents to assess the criteria for brain tumors. The assessment data from respondents was tested using the Cohen's kappa test to assess reliability between respondents and the Wilcoxon test to determine the level of difference in axial image diagnostic information, then the mean rank was used to determine sequences with better diagnostic image information.Results: The results of the study show that there is a difference in the diagnostic information of axial images on MRI brain examination between SWI and T2 FLASH 2D sequences in tumor cases with a p-value of 0.014. The significant difference is due to the susceptibility effect in both sequences. Based on the Wilcoxon test, the SWI sequence is the most optimal sequence in displaying diagnostic information with a mean rank value of 4.Conclusions: There is a difference of axial image diagnostic information between SWI and T2 FLASH 2D sequence in Brain MRI with brain tumors cases, and SWI sequence produces the most optimal axial image diagnostic information in MRI brain with brain tumor cases.